If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (12 + 6) + 1x = 3x + -12 Combine like terms: 12 + 6 = 18 (18) + 1x = 3x + -12 18 + 1x = 3x + -12 Reorder the terms: 18 + 1x = -12 + 3x Solving 18 + 1x = -12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 18 + 1x + -3x = -12 + 3x + -3x Combine like terms: 1x + -3x = -2x 18 + -2x = -12 + 3x + -3x Combine like terms: 3x + -3x = 0 18 + -2x = -12 + 0 18 + -2x = -12 Add '-18' to each side of the equation. 18 + -18 + -2x = -12 + -18 Combine like terms: 18 + -18 = 0 0 + -2x = -12 + -18 -2x = -12 + -18 Combine like terms: -12 + -18 = -30 -2x = -30 Divide each side by '-2'. x = 15 Simplifying x = 15
| (x^2y^2/x^4y^4)/(xy/x^2y^3) | | xi-6x+5=5 | | 5X^2-Y=10 | | (4u-2)(9-u)=0 | | X^2-1/6x | | -7x+20=3x+100 | | 12+1x+6=3x-12 | | 30=c/28 | | -21p=714 | | t+127=993 | | 24-4-8k= | | 22t=462 | | 96=-4n | | 84=3c | | g-14=46 | | m+31=-33 | | p/-4=10 | | 2x^2-12x=864 | | p-1=14 | | 91=s+26 | | 3=h/4 | | h/2=-3 | | -1=t/2 | | 6(y-4)+2y=72-8y | | 2=z-5 | | ln(2x+1)+ln(x-7)=lnx+ln(2x-3) | | (72000-64800/7200)*100 | | 4(3)-5=7 | | 63-3u=4u | | -2+3y=y-2-4t | | 3x+2+x=x-5 | | 18-(-x)=3 |